2004
DOI: 10.1074/jbc.m404838200
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Insulin-like Growth Factor-I (IGF-I) and Insulin Action by Mevalonic Acid Depletion

Abstract: High concentrations of statin were necessary to impair insulin-mediated glucose uptake (300 nM ‫؍‬ 33% ؎ 12% p < 0.05), and this process was not effected by farnesyl transferase inhibition. Gycosylation inhibitors mimicked the effect of statin treatment (tunicamycin p < 0.001, castanospermine p < 0.05, deoxymannojirimycin p < 0.05), and there was insulin proreceptor accumulation. These data imply that HMG-CoA reductase inhibitors disrupt IGF-I signaling by combined effects on Ras prenylation and IGF receptor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 50 publications
2
73
0
2
Order By: Relevance
“…We have previously shown that HMG-CoA reductase inhibitors are potent inhibitors of IGF signaling in 3T3-L1 preadi- pocytes (17), and so we next investigated whether cerivastatin would modulate inhibition of the osteogenic differentiation and mineralization of VSMCs by IGF. Fig.…”
Section: Hmg-coa Reductase Inhibitors Inhibit the Proliferation And Omentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that HMG-CoA reductase inhibitors are potent inhibitors of IGF signaling in 3T3-L1 preadi- pocytes (17), and so we next investigated whether cerivastatin would modulate inhibition of the osteogenic differentiation and mineralization of VSMCs by IGF. Fig.…”
Section: Hmg-coa Reductase Inhibitors Inhibit the Proliferation And Omentioning
confidence: 99%
“…IGFR Localization-To determine the effect of HMG-CoA reductase inhibitors on the cell-surface expression of the IGFR, confluent VSMCs (in T75 flasks) were treated with and without cerivastatin for 4 days, and membranes were prepared as described previously (17). Briefly, cells were washed three times with ice-cold PBS, scraped into 50 mM HEPES and protease inhibitor mixture (Calbiochem), and sonicated (3 ϫ 5 s, MSE sonicator, amplitude of 16 m).…”
Section: Proliferation Of Vsmcs-proliferation Of Vsmcs Was Assessed By [mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by decreasing FPP and subsequently dolichol synthesis, statins have an inhibitory effect on N-linked glycosylation 130 and therefore, insulin and Type 1 IGF-1 proreceptor cleavage may be impaired. In addition, statins possess both indirect and direct antioxidant activity 136 .…”
Section: Statinsmentioning
confidence: 99%
“…Dolichol, a product of the mevalonate pathway, is required for the maturation of insulin and Type 1 IGF-I receptors 120 . Specifically, dolichol acts as a carbohydrate donor during N-linked glycosylation of membrane-targeted proteins 130 . While this post-translational modification is not critical for most cell surface receptors, the Type 1 IGF and insulin receptors require glycosylation for proper proreceptor cleavage, without which the proreceptor is retained within the endoplasmic reticulum 131,132 ; thus dolichol is essential for insulin and IGF-I signaling.…”
Section: Statinsmentioning
confidence: 99%